Design and flight performance of hybrid underwater glider with controllable wings. (15th May 2017) - Wang, Yanhui; Zhang, Yiteng; Zhang, MingMing; Yang, Zhijin; Wu, Zhiliang
Hybrid underwater glider combines motion modes of traditional autonomous underwater glider and those of autonomous underwater vehicles. Different motion modes need different flight performance, including flight efficiency, static stability, and maneuverability. Conventional hybrid underwater glider with fixed wings can't achieve optimal flight performance in one flight mission demanding various motion modes. In this article, controllable wings for hybrid underwater glider Petrel II are designed. Angle of attack, sweep angle, and aspect ratio of controllable wings can be changed to adapt to different motion modes. Kinematics and dynamics models of Petrel II are established based on multibody theory. Motion simulations of Petrel II with different wing configurations are conducted in three motion modes, including glide motion, spiral motion, and horizontal turning motion. The simulation results show the impact of wing parameters on flight performance. Field trials demonstrate that the controllable wings can improve the flight performance.